LIFELONG EDUCATION BETWEEN THE USEFUL AND THE USELESS : LEARNING CITY TOPONYMY - Piccinini, Livio Clemente; Mario, Taverna; Tubaro, Giovanni (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the paper is to discuss the balance between the useful and the useless in the actual lifelong learning, in a conceptual scheme that goes beyond purely economical or technical evaluations. The authors chose an exemplary field starting from last year’s paper on the exploration of nets. In order to delimitate the research field, the official city toponymy has been considered, both in the structure of hypernyms and in the choices of proper names. The analysis considers Italian city hypernyms, with some regional or local varieties, explaining the underlying historical and contact phenomena. The grouping of similar proper names is then analyzed, finding out segmentations and some strange aversions. The non correspondence between the conceptual hierarchy and the perceptual geographical hierarchy is highlighted. Useful practical reference systems are compared with official ones.